Changes in the digestive gland of Euphausia superba during short-term starvation: lipid class, fatty acid and sterol content and composition - Patti Virtue; Nicol, S; Nichols, P (1993)
During a period of short-term (19 d) starvation, total lipid in the digestive gland of Euphausia superba Dana decreased from 21 to 9% dry weight. Total lipid per digestive gland decreased significantly during starvation compared to Day 0 individuals, falling from 1960 (_+ 172) to 385 (_+81)gg. Polar lipid was the major lipid class utilised during starvation, falling from 1510 (,.-225) to 177 (__ 46) gg per digestive gland (76 to 45 %). Absolute levels of triacylglycerol fell from 300 (_+41) to 76 (_+5) gg; however, relative levels remained unchanged. The relative level of free fatty acid increased significantly with starvation (4 to 39 %) with absolute levels ranging from 79 (+ 1) to 156 (_+20) ~tg per digestive gland. Absolute levels of all fatty acids per digestive gland declined continually until the end of the starvation period. The long-chain polyunsaturated acids eicosapentaenoic (20:50)3) and docosahexaenoic (22:60)3), decreased with starvation from 37 to 26% and 15 to 10%, respectively whereas the saturated fatty acid, palmitic acid (16:0), increased from 15 to 22%. Cholesterol, the major sterol in this organ, increased from 17 (+ 20) to 44 (___ ] 3) gg per digestive gland by Day 3, and by Day 19 had returned to levels found in the digestive gland of Day 0 individuals. Desmosterol followed a similar pattern to cholesterol, increasing from 3 (__ 1) l~g per digestive gland on Day 0 to 11 (+_4) gg on Day3, and falling to 2 (+-l)Bg on Day 19. Other sterols in the digestive gland, predominantly of algal origin, fell from the levels found in Day 0 individuals to near zero amounts by Day 6. The digestive gland of E. superba plays a dynamic role during shortterm starvation in terms of lipid content and composition. The relative levels of polar lipids, free fatty acids and cholesterol in the digestive gland may provide reliable indices of the nutritional condition of E. superba in the field. Sterols in the digestive gland are indicative of recent dietary composition of krill, and may also be used to quantify ...